Acting Like a Baby Boomer? Birth-Cohort Differences in Adults' Personality Trajectories During the Last Half a Century. (March 2022) - Brandt, Naemi D.; Drewelies, Johanna; Willis, Sherry L.; Schaie, K. Warner; Ram, Nilam; Gerstorf, Denis; Wagner, Jenny
Society and developmental theory generally assume that there are wide generational differences in personality. Yet evidence showing historical change in the levels of adult Big Five traits is scarce and particularly so for developmental change. We tracked adult trajectories of personality in 4, 732 participants (age: M = 52.93 years, SD = 16.69; 53% female) from the Seattle Longitudinal Study (born 1883–1976) across 50 years. Multilevel models revealed evidence for historical change in personality: At age 56, later-born cohorts exhibited lower levels of maturity-related traits (agreeableness and neuroticism) and higher levels of agency-related traits (extraversion and openness) than earlier-born cohorts. Historical changes in agreeableness and neuroticism were more pronounced among young adults, but changes in openness were less pronounced. Cohort differences in change were rare and were observed only for agreeableness; within-person increases were more pronounced among later-born cohorts. Our results yield the first evidence for historical change in the Big Five across adulthood and point to the roles of delayed social-investment and maturity effects.